2017
DOI: 10.1093/jxb/erx269
|View full text |Cite
|
Sign up to set email alerts
|

The cell wall of Arabidopsis thaliana influences actin network dynamics

Abstract: Number of tables: 3Word count: 5624 words Number of supplementary items: 7 Running titleCell wall affects actin cytoskeleton dynamics in A. thaliana HighlightActin cytoskeleton dynamics, as quantified with two new image analysis tools, were reduced in plasmolysed cells and cells treated with isoxaben to disrupt cell wall structure. AbstractIn plant cells, molecular connections link the cell wall-plasma membrane-actin cytoskeleton to form a continuum. It is hypothesised that the cell wall provides stable anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Increase in immobility may be connected with enhanced internalization in case of At HIR1–YFP and with accumulation of At FLOT2–GFP into sparser but more pronounced domains in these conditions. Plasmolysis induced by similar concentrations of mannitol or sorbitol caused dramatic changes in several cellular processes including reduced movement of endoplasmic reticulum structures (Cheng et al , ) or decreased actin dynamics (Tolmie et al , ) and polymerization (Yu et al , ). It is therefore possible that reported increase in mobility may not be a direct effect of PM detachment but rather a result of complex changes induced by plasmolysis in a cell which probably involve also cytoskeleton dynamics alteration that were in many cases also documented to affect PM protein mobility (see the Discussion above).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in immobility may be connected with enhanced internalization in case of At HIR1–YFP and with accumulation of At FLOT2–GFP into sparser but more pronounced domains in these conditions. Plasmolysis induced by similar concentrations of mannitol or sorbitol caused dramatic changes in several cellular processes including reduced movement of endoplasmic reticulum structures (Cheng et al , ) or decreased actin dynamics (Tolmie et al , ) and polymerization (Yu et al , ). It is therefore possible that reported increase in mobility may not be a direct effect of PM detachment but rather a result of complex changes induced by plasmolysis in a cell which probably involve also cytoskeleton dynamics alteration that were in many cases also documented to affect PM protein mobility (see the Discussion above).…”
Section: Discussionmentioning
confidence: 99%
“…The plant cell wall is also required for normal localisation of PIN2 in the membrane and hence regulation of cell polarity (19). These examples highlight the possibility that the components of the cytoskeleton / PM / cell wall continuum can regulate each other, with cell-wall regulation of plasma-membrane, and cytoskeleton organization already observed (5, 20).…”
Section: Introductionmentioning
confidence: 63%
“…This continuum is presumably responsible for transmitting cell wall perturbations to the cytoskeleton resulting in reorganisation. In this respect, Tolmie et al [92] reported an increase in actin network stability in plasmolysed cells or cells treated with isoxaben, a cellulose synthesis inhibitor, and normal dynamics were recovered in re-hydrated cells, demonstrating changes in actin cytoskeleton dynamics were highly correlated with cell wall disruption. In combination, these findings suggest a role of the plant cytoskeleton in regulating cell wall biosynthesis by determining cellulose deposition sites and cellulose microfibril orientation through the cytoskeleton-plasma membrane-cell wall continuum.…”
Section: Actin Filaments and Microtubules Act Together To Deliver Cscmentioning
confidence: 99%